PENGARUH LATIHAN DOUBLE LEG BOUND TERHADAP DAYA LEDAK OTOT TUNGKAI PADA TIM BOLA VOLI PUTRI IVODA (IKATAN VOLI DAERAH) PEKANBARU - Lisdawati Lisdawati; Ramadi Ramadi; Ardiah Juita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: Based on the background of the problems above, you can identify this issue is: is There a Double leg exercises influence bound against an explosive limb muscles in the Volleyball Team's daughter IVODA (Regional Volleyball Bond) Soweto, population in this research is the volleyball team of Princess IVODA of Pekanbaru that add up to 10 people. Data obtained as a result of the research is data quality through a test before and after giving a Double leg exercises baund treatment. The data is taken through a test and measurement against 10 men athletes team ball voliputri Ivoda Pekanbaru. The variables in this study i.e. double leg exercises baundyang denoted by (X) as a free variable. While the power of the limb muscles (Y) as a variable.The hypothesis tested in this research is the influence of the Double leg exercises baund method against power volleyball team limb muscles of Princess Ivoda of Pekanbaru. To test whether the hypothesis presented in this study received its existence or not then performed testing data memakaiuji t sample of bound. From the analysis performed, the values between the beginning and end of the test the test latihanDouble leg baund against power showed that value (9.48) (1,833), it can be concluded that the hypothesis that States there is a Double leg exercises influence baund against muscle power limb Ivoda daughter volleyball team (ties volleyball area) Pekanbaru.Key Words: Exercise Double Leg Bound, Explosive Limb Muscles